Amyloid and Light Chain Deposition Disorders - Baqir, Misbah; Moua, Teng; Ryu, Jay H (Clinics in chest medicine, 2025)
Amyloidosis and Light Chain Deposition Disease (LCDD) are disorders characterized by the deposition of abnormal proteins in tissues, leading to organ damage. Pulmonary involvement in amyloidosis can manifest as diffuse alveolar-septal amyloidosis, nodular or cystic pulmonary amyloidosis, or tracheobronchial involvement. The types of amyloidosis-immunoglobulin light chain), serum amyloid A, and transthyretin (ATTR)-affect the lungs differently, with ATTR being rare. LCDD, which primarily affects the kidneys, may also cause lung abnormalities, such as cystic or nodular disease. Both conditions are diagnosed through biopsy and imaging, with therapies targeting the underlying plasma cell or inflammatory disorders.